Revolutionizing Primary Education Assessment: Opportunities and Challenges in Bandar Lampung's Technology-Driven Landscape - Nurul Hidayah; Agus Pahrudin; Tri Anjar (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This study aims to analyze the opportunities and challenges associated with implementing a technology and information-based educational assessment system in elementary schools in Bandar Lampung. The study recruited ten respondents who were IT staff members, teachers, and principals from upper-grade primary levels (grades IV, V, and VI). It used a qualitative descriptive research design. The research focused on identifying the opportunities and challenges related to IT-based assessment systems. Data collection methods included observations, interviews, and documentation, while data analysis was conducted using the Miles and Huberman model, encompassing data reduction, data display, and data verification. The findings reveal significant opportunities in adopting a technology-based assessment system, such as using Google Forms for flexible assessment scheduling and enhanced data analysis capabilities afforded to teachers through IT tools. However, notable challenges were also identified, including insufficient IT proficiency among teachers and staff, concerns over data privacy and protection, and inadequate internet connectivity within school premises, which hampers the effective use of IT-based applications. The study recommends that schools provide intensive training for teachers and staff to enhance their IT skills. The conclusion is that while technology-based assessment systems offer considerable advantages in facilitating teachers' tasks, the identified challenges must be addressed to optimize the benefits and overcome the obstacles encountered.